2018
DOI: 10.1371/journal.pone.0208748
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior impacts on dietary water intake and hydration status in Spanish schoolchildren: A cross-sectional study

Abstract: BackgroundThe importance of maintaining an adequate hydration status and the complexity of the water balance make it necessary to study the lifestyle factors that can influence or modify these variables. The aim of this study was to evaluate the hydration status and dietary water intake for a sample of Spanish schoolchildren from 7 to 12 years old and their associations with physical activity (PA) and sedentary behaviors.MethodsA total of 242 schoolchildren was studied (49.17% females). A 24-hour urine sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This phenomenon was similar to some studies in Spain. Perales-García et al [ 22 ] found less than half of youths had adequate water, and Finnish females between the ages of 12 and 17 years tended to be inactive [ 23 ]. As Silk and Kwok [ 13 ] mentioned, oral disease can have a profound effect on overall health but is one of the most unmet healthcare needs of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was similar to some studies in Spain. Perales-García et al [ 22 ] found less than half of youths had adequate water, and Finnish females between the ages of 12 and 17 years tended to be inactive [ 23 ]. As Silk and Kwok [ 13 ] mentioned, oral disease can have a profound effect on overall health but is one of the most unmet healthcare needs of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methodology have been previously described [17][18][19]. The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the Ethics Committee for Clinic Review of the Clinic San Carlos Hospital, which is part of the Universidad Complutense de Madrid (Madrid, Spain) (Ref 12/319-E and 15/522-E).…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of subjects with optimal hydration status was only 15.6%, which is much lower than that of young male and female adults in China [ 42 ], revealing the athletes are more likely to be dehydrated. Similarly, in one study conducted on schoolchildren with physical activity and sedentary behavior in Spain, it was revealed that children who were more inactive were adequately hydrated [ 43 ]. Recent data reported that athletes are subjected to the adverse effects of dehydration.…”
Section: Discussionmentioning
confidence: 99%